Quedas em idosos brasileiros: morbimortalidade e projeção de internações no Estado do Rio Grande do Sul (1998-2020). - Barros, Iarema Fabieli Oliveira de (2016)
Population aging is a global reality. Initially observed in developed countries, today presents intensively in developing countries. Brings with it many concerns to managers, as is becoming a public health problem, especially when considering the external causes of morbidity and mortality, especially falls. This research aims to evaluate the morbidity and mortality due to falls in elderly Brazilians and analyze the temporal trend of hospital admissions for people aged sixty or older, residing in the State of Rio Grande do Sul (RS), from 1998 to 2012 and were drawn their projections relative and absolute, by the year 2020. This study consists of three articles. The former is a reflection article about the human aging process, the second, an integrative review of literature on the morbidity and mortality due to falls in elderly Brazilians and the third refers to the temporal trend and projection of hospital admissions by falls for elderly residents in the RS. This study did not require submission to the Research Ethics Committee (CEP) of the Universidade Federal de Santa Maria (UFSM) because it is a search using secondary data in the public domain, available online at DATASUS (www.datasus.gov.br) and thus there is no variables that allow the identification of the research subjects.